Analisis DuPont untuk Mengukur Kinerja Keuangan pada Agroindustri Tahu Bulat Putra Mandiri di Dusun Buniasih Desa Muktisari Kecamatan Cipaku Kabupaten Ciamis - Adenty Oktavianty; Wilva Ramadayanti; Andena Nur Hikmatunnisa; Aini Dewi Maryan; Riantin Hikmah Widi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Agroindustry plays a crucial role in the economy, particularly in supporting food security and creating business opportunities in rural areas. However, to remain competitive in an increasingly challenging market, a comprehensive evaluation of financial performance is essential. This study aims to analyze the financial performance of the Tahu Bulat Agroindustry in Buniasih Hamlet, Muktisari Village, Cipaku Subdistrict, Ciamis Regency, using the Du Pont System approach over the 2022–2024 period. The analysis focuses on five key indicators: Assets Turnover, Net Profit Margin, Return on Investment (ROI), Equity Multiplier, and Return on Equity (ROE). The results reveal an average Assets Turnover of 1.42 times, indicating effective asset utilization in generating sales. The average Net Profit Margin of 17.80% reflects the company’s ability to generate net profit from sales. The average ROI of 25.55% indicates efficient asset utilization. The Equity Multiplier has an average of 4.77 times, demonstrating the contribution of the capital structure to asset management. Meanwhile, the average ROE of 125.54% highlights high returns on equity, despite significant declines in the final year. The study concludes that the financial performance of the agroindustry is generally good, but declining indicators in the last year require strategies to improve efficiency and asset management. It is recommended that the company reevaluate its capital structure and enhance operational efficiency to ensure business sustainability.